Impact of supplemental immunisation activity (SIA) campaigns on health systems: findings from South Africa. Issue 11 (23rd August 2013) - Verguet, Stéphane; Jassat, Waasila; Bertram, Melanie Y; Tollman, Stephen M; Murray, Christopher J L; Jamison, Dean T; Hofman, Karen J
Abstract : Background: Supplemental immunisation activity (SIA) campaigns provide children with an additional dose of measles vaccine and deliver other child health interventions including vitamin A supplements, deworming medications and oral polio vaccines. They also require the mobilisation of a large health workforce. We assess the impact of the implementation of SIA campaigns on selected routine child and maternal health services in South Africa (SA). Methods: We use district-level monthly headcount data for 52 South African districts for the period 2001–2010, sourced from the District Health Information System, SA. The data include 12 child and maternal health headcount indicators including routine immunisation, and maternal and reproductive health indicators. We analyse the association between the implementation of the 2010 SIA campaign and the change (decrease/increase) in headcounts, using a linear regression model. Results: We find a significant decrease for eight indicators. The total number of fully immunised children before age 1 decreased by 29% (95% CI 23% to 35%, p<0.001) during the month of SIA implementation; contraceptive use and antenatal visits decreased by 7–17% (p ≤ 0.02) and about 10% (p<0.001), respectively. Conclusions: SIA campaigns may negatively impact health systems during the period of implementation by disrupting regular functioning and diverting resources from other activities, including routine child and maternal health services. SIA campaigns present multidimensional costs that need to be explicitly considered in benefit–cost assessments.